네 가지 빛간섭단층혈관조영술 기기의 망막혈관 밀도와 망막중심오목무혈관부위의 크기 분석 - 박서연(Seo Yeon Park), 남기태(Ki Tae Nam), 윤철민(Cheolmin Yun), 장성민(Sungmin Jang) (Daihan angwa haghoi jabji, 2020)
목적: 네 가지 다른 빛간섭단층혈관조영술 영상의 망막혈관 밀도 및 망막중심오목무혈관부위를 비교하고자 하였다. 대상과 방법: 전향적 연구로, 건강한 성인을 대상으로 Plex-Elite (Carl Zeiss), DRI OCT-1 Atlantis (Topcon), AngioPlex (Carl Zeiss), Spectralis OCTA (Heidelberg) 기기를 이용하여 얻은 황반 중심 3 x 3 mm2 영상의 망막혈관 밀도와 중심오목무혈관부위의 크기를 분석하였다. 결과: 표층 및 심부모세혈관총의 망막혈관 밀도(%)는 Plex-Elite (42.17 ± 2.79, 43.71 ± 2.36), DRI OCT-1 Atlantis (28.70 ± 2.87, 30.27 ± 3.02), AngioPlex (28.32 ± 6.68, 33.33 ± 5.44), Spectralis OCTA (27.86 ± 4.13, 28.54 ± 3.14)로, 기기 간 차이가 있었고(p<0.001), 표층 및 심부모세혈관총의 중심오목무혈관부위의 크기(mm2)는 각각 Plex-Elite (0.276 ± 0.097, 0.340 ± 0.100), DRI OCT-1 Atlantis (0.281 ± 0.102, 0.354 ± 0.119), AngioPlex (0.269 ± 0.099, 0.422 ± 0.120), Spectralis OCTA (0.272 ± 0.079, 0.298 ± 0.106)로, 기기 간 차이를 보였다(p<0.001). 표층 및 심부모세혈관총 망막혈관 밀도 모두 네 가지 기기 간 유의한 상관관계를 보이지 않았으나(p>0.05), 망막중심오목무혈관부위 면적은 표층 및 심부모세혈관총 모두에서 네 가지 기기 간의 통계적으로 유의한 양의 상관관계를 보였다(p<0.001). 결론: 네 가지 빛간섭단층혈관조영술 기기를 이용한 망막혈관 밀도와 망막중심오목무혈관부위 면적은 기기 간 차이가 있었으며, 영상을 분석하는 데 있어 이러한 차이를 고려해야 할 것으로 판단된다. Purpose: To compare the vessel density (VD) and foveal avascular zone (FAZ) area using four different optical coherence tomography angiography (OCTA) images. Methods: This prospective study analyzed the OCTA images of consecutive healthy subjects using Plex-Elite (Carl Zeiss), DRI OCT-1 Atlantis (Topcon), AngioPlex (Carl Zeiss), and Spectralis OCTA (Heidelberg Engineering). The VD and FAZ areas were calculated using the OCTA images with a 3 x 3 mm2 volume scan pattern centered on the fovea. Results: The VD (%) of the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were different using the four devices: Plex-Elite (42.17 ± 2.79, 43.71 ± 2.36), DRI OCT-1 Atlantis (28.70 ± 2.87, 30.27 ± 3.02), AngioPlex (28.32 ± 6.68, 33.33 ± 5.44), and Spectralis OCTA (27.86 ± 4.13, 28.54 ± 3.14), respectively; p < 0.001). The FAZ area (mm2) of the SCP and DCP were different using the four devices: Plex-Elite (0.276 ± 0.097, 0.340 ± 0.100), DRI OCT-1 Atlantis (0.281 ± 0.102, 0.354 ± 0.119), AngioPlex (0.269 ± 0.099, 0.422 ± 0.120), and Spectralis OCTA (0.272 ± 0.079, 0.298 ± 0.106), respectively; p < 0.001). The VD of the SCP and DCP had no significant correlation using the four devices (all, p > 0.05), but the FAZ area had positive correlations using the four devices (all, p < 0.001). Conclusions: The four OCTA devices provided different VD and FAZ areas, so these differences should be considered in analyzing OCTA images. KCI Citation Count: 0